Can different formulae be used in the diagnosis and staging of chronic kidney disease? - Çam Ergin; Kural Alev; Yılmaz Mürvet (Türk Biyokimya Dergisi)
Chronic kidney disease (CKD), which has a significant prevalence of 15.7 % in Turkey, is a global health problem that particularly affects elderly. It is difficult to distinguish between age-related and CKD-related declines in kidney function with current glomerular filtration rate (GFR) estimation methods. The “HUGE” formula, incorporating haematocrit, urea, and gender, offers improved differentiation, targeting individuals over 40. This study aims to evaluate the effectiveness of the HUGE formula in estimating GFR in this demographic group and to establish a better diagnostic threshold.